Photoelectrocatalytic Decolorization of Reactive Brilliant Red X-3B - Fang, Tao; Liao, Lixia; Zhan, Sanhong; Wu, Xiaoliang (Asian Journal of Chemistry, 2012)
The RuO2/TiO2 photo electrode and stainless steel net cathode were prepared by dip-coating method, respectively. The electricity assisted photocatalytic system was built up by using UV high pressure mercury lamp as the light source, RuO2/TiO2 electrode as photo anode, stainless steel net as counter electrode and reactive brilliant red X-3B(X-3B) as the synthetic wastewater. Various factors, such as different degradation methods, the chloride concentration, applied current and original pH value that influences the photoelectrocatalytic decomposition of X-3B dye, have been studied. The decolorization ability of photoelectrocatalytic degradation X-3B compared with the photocatalytic degradation and the electrochemical degradation. The results showed that photocatalytic and electrochemical oxidation has a synergistic effect on decolorization of X-3B. The possible roles of the electrolyte on the reactions and the probable mechanisms of effect were also discussed.